The Inhibitory Effect of Wheat Husks Addition on Aflatoxins Production by Aspergillus flavus in Liquid Culture With Various Wheat Compositions as Carbon Sources - Ghanem, Khaled M.; Lotfy, Walid A.; El-Shaer, Mohamed M.; Elassar, Samy A. (Frontiers in Microbiology, 2020)
Wheat may be infected by the aflatoxigenic mould Aspergillus flavus during pre- and post-harvest activities. Control strategies reported to manage aflatoxin contamination of wheat are expensive and require extensive testing to verify absence of toxic secondary metabolites or newly formed compounds. The objective of this study was to develop an in-vitro new control strategy based on assessing the influence of wheat husks on aflatoxins production by A. flavus in liquid culture. The results showed that aflatoxins production was significantly influenced by the existence of husks in the wheat forms used as carbon substrates according to the following order: full wheat grains < half crushed wheat grains < wheat flour 82% < wheat flour 72%. By applying a fractional factorial design and a response surface methodology, a maximum aflatoxins production (2.567 ng/mg) was predicted when wheat flour 72% (39 g/l), as a carbon source, yeast extract (5 g/l), and 75 ml medium volume /250 ml flask were utilized. At this optimized condition, after addition of ground wheat husks, the growth and synthesis of aflatoxins of A. flavus were repressed by 74.85 and 98.72%, respectively. This finding paved the way to examine the anti-fungal potential of wheat husks constituents and to compare their efficacy with thyme, cinnamon, sweet basil and coriander essential oils which possess antimycotic activities. Accordingly, the wheat husks component SiO2 showed the highest growth inhibition (67.04%) and reduction of A. flavus aflatoxins (82.67%). These results were comparable to those obtained from various examined antimycotic essential oils.